Innovation in Malmö after the Öresund Bridge - Olof Ejermo; Katrin Hussinger; Basheer Kalash; Torben Schubert (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We analyze the effect of the Öresund Bridge, a combined railway and motorway bridge between Swedish Malmö and the Danish capital Copenhagen, on inventive activity in the region of Malmö. Applying difference-in-difference estimation on individual-level data, our findings suggest that the Öresund Bridge led to a significant increase in the number of patents per individual in the Malmö region as compared to the two other major regions in Sweden, Gothenburg and Stockholm. We show that a key mechanism is the attraction of highly qualified workers to the Malmö region following the construction of the bridge.
Keywords: O31; O33; R11; L91; 330; transportation infrastructure; innovation; Öresund Bridge; cross-border regions; patents; inventors; agglomeration effects